Extending the EU Renewable Energy Directive sustainability criteria to solid bioenergy from forests. (22nd April 2014) - Fritsche, Uwe R.; Iriarte, Leire; de Jong, Johnny; Agostini, Alessandro; Scarlat, Nicolae
Abstract Solid bioenergy from forests plays — and is expected to continue to play — a key role to fulfil the renewable energy targets at the European Union level. When the Renewable Energy Directive was enacted, sustainability criteria were incorporated solely for biofuels and bioliquids. Sustainability criteria for solid bioenergy are also needed in order to prevent wood and primary forest residues from posing additional environmental risks to ecosystems. Acknowledging this, the European Commission has been working on extending the biofuels and bioliquids provisions to solid biomass. An internal draft was circulated in August 2013 which addressed the ways to both balance and mitigate the risks in three main topics: biodiversity; sustainable forest management; and greenhouse gases. This paper presents a set of criteria and indicators, developed during workshops with experts from Governments, scientific institutions, businesses and NGOs, that may be considered by the EU to assure that solid biomass from forests is obtained in an environmentally sustainable way.